A microsphere-coated keratinase-targeted delivery formulation that responds to the intestinal environment and its preparation process.

CN122937025APending Publication Date: 2026-10-20XINYUAN BETA (CHENGDU) BIOTECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611442372.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-17
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

[0005]因此,本发明提供了一种通过肠道环境响应的微球包覆角蛋白酶靶向递送制剂及其制备工艺,解决现有技术中角蛋白酶易失活,以及微球外层难以兼顾胃部抗酸屏障与肠道快速崩解的结构控制难题

Benefits of technology

[0016]本发明有益效果为:通过构建内层多孔骨架与天然蛋白外层,改善角蛋白酶在加工中易发生空间结构塌陷而失活的问题,以及微球难以兼顾胃部强效抗酸与肠道极速崩解的物理结构控制难题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

This invention relates to the field of biopharmaceutical technology and discloses a microsphere-encapsulated keratinase targeted delivery formulation that responds to the intestinal environment and its preparation process. By constructing a low-temperature physically cross-linked inner porous framework and a controlled-encapsulation outer layer of natural protein, this invention overcomes the challenges of keratinase's tendency to collapse and become inactive during processing, as well as the structural control difficulties of microspheres in simultaneously achieving strong gastric acid resistance and rapid intestinal disintegration. This results in high activity retention and intestinal-targeted delivery of keratinase.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of biopharmaceutical technology, and more specifically, to a microsphere-coated keratinase targeted delivery formulation that responds to the intestinal environment and its preparation process. Background Technology

[0002] Keratinase, a specific biocatalyst capable of efficiently degrading keratin in coarse hair and dandruff, is widely used in areas such as high-protein nutrient digestion in pets, prevention of hairballs, and skin health care. However, due to the complex physiological characteristics of pets' digestive tract, unprotected keratinase is easily inactivated by high concentrations of gastric acid and potent pepsin when passing through the stomach. To overcome this technical challenge, encapsulating keratinase in microspheres using polymer materials to achieve targeted delivery formulations that precisely respond to the intestinal environment has gradually become a core research direction in the pet pharmaceutical manufacturing industry.

[0003] However, in the actual industrial manufacturing and application, this industry still faces many technical challenges. Keratinase is a protein macromolecule that is highly sensitive to temperature, moisture, and shear force. Existing conventional microsphere preparation or coating processes often involve high-temperature drying, vigorous mechanical stirring, or soaking in high-concentration organic solvents, which can easily lead to denaturation and collapse of the enzyme's three-dimensional structure, resulting in low activity recovery rates in the finished product. In addition, the gastrointestinal environment of pets has unique physiological fluctuations. The pH value of their stomach is greatly affected by the form of food and stress, and their intestines are relatively short with rapid passage of contents. This requires that the response barrier on the outer layer of the microspheres must have both acid resistance and rapid release of active enzymes. Existing technologies often compromise one aspect for the other. Strengthening the resistance to gastric acid often leads to difficulty in intestinal disintegration, while increasing the disintegration rate can lead to premature leakage in the stomach. This structural control problem, which is difficult to balance, has become a key technical bottleneck hindering the high-quality industrialization of intestinal environment-responsive keratinase microsphere formulations. Summary of the Invention

[0004] In view of the aforementioned existing problems, the present invention is proposed.

[0005] Therefore, this invention provides a microsphere-coated keratinase targeted delivery formulation and its preparation process that responds to the intestinal environment, solving the problems of easy inactivation of keratinase in the prior art and the difficulty in controlling the structure of the outer layer of the microsphere to simultaneously protect the gastric acid barrier and prevent rapid intestinal disintegration.

[0006] To solve the above-mentioned technical problems, the present invention provides the following technical solution: This invention provides a method for preparing a microsphere-coated keratinase-targeted delivery formulation that responds to the intestinal environment, comprising the following steps: S1. By weight, add 75-85 parts sodium alginate, 2-5 parts trehalose and 10-20 parts keratinase to the liquid medium and homogenize and stir at 100-500 rpm for 30-50 min to obtain the liquid enzyme dispersion. S2. Lower the system temperature, add the liquid enzyme dispersion to 0.5-2 parts of calcium ion aqueous solution and solidify for 20-40 min. Wash the solidified microspheres to obtain washed microspheres. S3. The washing microspheres are spread out and fed into a freeze dryer for freeze drying. They are pre-frozen in situ at -50~-30 ℃, and then the temperature of the partition is raised to -20~0 ℃ under vacuum for dehydration and drying to obtain porous framework microspheres. S4. Dissolve and homogenize 10-20 parts of corn gluten and 1-5 parts of fucoidan in a 70% ethanol aqueous solution to obtain a coated fluid; S5. Control the surface temperature of the material, spray the coating fluid onto the porous skeleton microspheres, and control the outer coating to be 15-25 parts. After in-situ cold air continuous fluidization drying, the finished double-layer microspheres are obtained.

[0007] As a preferred embodiment of the method for preparing a microsphere-coated keratinase-targeted delivery formulation that responds to the intestinal environment according to the present invention, in step S1, the sodium alginate is 81 parts by weight, the trehalose is 3 parts by weight, and the keratinase is 15 parts by weight; the homogenization stirring parameters are 300 rpm for 40 min.

[0008] As a preferred embodiment of the method for preparing a microsphere-coated keratinase targeted delivery formulation that responds to the intestinal environment according to the present invention, in step S2, the calcium ion aqueous solution is 1 part by weight; and the curing time is 30 min.

[0009] As a preferred embodiment of the method for preparing a microsphere-coated keratinase targeted delivery formulation that responds to the intestinal environment according to the present invention, in step S3, the in-situ pre-freezing temperature is -40 ℃ and the dehydration drying temperature is -10 ℃.

[0010] As a preferred embodiment of the method for preparing a microsphere-coated keratinase-targeted delivery formulation that responds to the intestinal environment according to the present invention, in step S4, the weight parts of the keratin are 15 parts and the weight parts of the brown algae oligosaccharide are 2.5 parts.

[0011] As a preferred embodiment of the method for preparing a microsphere-coated keratinase targeted delivery formulation that responds to the intestinal environment according to the present invention, in step S2, the system temperature needs to be reduced to 0~4 ℃.

[0012] As a preferred embodiment of the method for preparing a microsphere-coated keratinase targeted delivery formulation that responds to the intestinal environment according to the present invention, in step S2, the washing process is as follows: the microspheres are filtered out and rinsed three times consecutively with cold purified water at 4 °C.

[0013] As a preferred embodiment of the method for preparing a microsphere-coated keratinase-targeted delivery formulation that responds to the intestinal environment according to the present invention, wherein: in step S3, the parameters for freeze-drying are: The first stage involves in-situ pre-freezing at a cooling rate of 1.0~2.0 ℃ / min for 2~4 h; the second stage involves starting the vacuum pump to reduce the system vacuum to 10~20 Pa and performing sublimation drying for 12~24 h; finally, the system vacuum is reduced to 1~5 Pa and a second drying is performed for 4~8 h.

[0014] As a preferred embodiment of the method for preparing a microsphere-coated keratinase targeted delivery formulation that responds to the intestinal environment according to the present invention, in step S5, the surface temperature of the controlled material is controlled at 15~18 ℃, and the in-situ cold air continuous fluidization drying time is 15 min.

[0015] This invention also provides a microsphere-coated keratinase-targeted delivery formulation that responds to the intestinal environment, prepared by the above method, wherein: the keratinase-containing bilayer microspheres have a core-shell nested three-dimensional structure, with a porous network formed by the physical coordination of sodium alginate and calcium ions and the interpenetration of trehalose molecules as the inner matrix framework; keratinase entities are uniformly distributed in the spatial channels of the porous network in a free state; hydrophobic zein macromolecular segments are physically interwoven and wrapped around the outer layer of the inner matrix framework to form a dense enteric coating, and fucoidan oligosaccharides are embedded and sealed within the microscopic topological defects of the dense outer coating.

[0016] The beneficial effects of this invention are: by constructing an inner porous framework and a natural protein outer layer, it improves the problem that keratinase is prone to spatial structure collapse and inactivation during processing, as well as the problem of physical structure control that makes it difficult for microspheres to simultaneously achieve strong acid resistance in the stomach and rapid disintegration in the intestine.

[0017] Specifically, this process uses a sodium alginate system as the inner framework, utilizing trehalose to provide in-situ support for the interconnecting channels. Keratinase is dispersed at 15–20 °C, and then solidified by being dropped into a 4 °C environment. This avoids damage to the three-dimensional structure of the enzyme molecules caused by high temperatures, and the initial activity of the enzyme is locked and preserved through a three-dimensional network structure. Based on this, freeze-drying dehydration creates a highly porous physical morphology for the inner microspheres, ensuring rapid disintegration of the microspheres in the intestine. Finally, zein is densely encapsulated on the outside of the microspheres at 15–18 °C. The use of fucoidan intercalation and sealing of microscopic topological defects during the zein film formation process prevents secondary inactivation caused by high-temperature film formation. This outer shell effectively blocks gastric acid and rapidly disintegrates upon entering the intestine. The synergistic effect of the inner and outer double-layer physical structures achieves targeted intestinal delivery of keratinase. Attached Figure Description

[0018] To more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings used in the following description of the embodiments will be briefly introduced. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0019] Figure 1 Figure 1 shows the results of optimizing the ratio of trehalose to calcium ions. (a) represents the compressive yield strength, and (b) represents the physical retention rate of the three-dimensional micropores.

[0020] Figure 2 Figure 2 shows the results of optimizing the ratio of trehalose to calcium ions.

[0021] Figure 3 Figure 1 shows the results of optimizing the ratio of zeaxanthin to brown algae oligosaccharides.

[0022] Figure 4 The second figure shows the results of optimizing the compound ratio of corn gluten and brown algae oligosaccharides. (a) is the time consumed for the dissociation of the weakly basic phase, and (b) is the anti-cracking strain rate.

[0023] Figure 5 Figure 1 shows the results of the optimization of stirring speed and time. (a) shows the viscosity retention rate, and (b) shows the enzyme spatial conformation retention rate.

[0024] Figure 6 The second figure shows the results of the optimized mixing speed and time.

[0025] Figure 7 The result diagram shows the optimization of the curing time.

[0026] Figure 8 Figure 1 shows the results of the processing optimization for pre-freezing temperature and drying temperature. (a) represents the space collapse rate, and (b) represents the wear-resistant crushing rate.

[0027] Figure 9 Figure 2 shows the results of the optimized processing of pre-freezing and drying temperatures.

[0028] Figure 10 The result of optimizing the weight gain rate of the outer coating is shown in the figure.

[0029] Figure 11 This is a flowchart illustrating the preparation method of a microsphere-coated keratinase targeted delivery formulation that responds to the intestinal environment. Detailed Implementation

[0030] To make the above-mentioned objects, features and advantages of the present invention more apparent and understandable, the specific embodiments of the present invention will be described in detail below with reference to the accompanying drawings.

[0031] Many specific details are set forth in the following description in order to provide a full understanding of the invention. However, the invention may also be practiced in other ways different from those described herein, and those skilled in the art can make similar extensions without departing from the spirit of the invention. Therefore, the invention is not limited to the specific embodiments disclosed below.

[0032] Secondly, the term "one embodiment" or "example" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the invention. The appearance of an embodiment in different places in this specification does not necessarily refer to the same embodiment, nor is it a single or selective embodiment that mutually excludes other embodiments.

[0033] Example 1

[0034] This embodiment aims to explore a raw material formulation system for a microsphere-encapsulated keratinase-targeted delivery formulation that responds to the intestinal environment, solving the structural control problems in the prior art, such as the easy inactivation of keratinase and the difficulty in simultaneously addressing the gastric acid barrier and rapid intestinal disintegration of the microsphere outer layer.

[0035] 1.1 Selection of main framework materials

[0036] In microsphere targeted delivery systems, the inner main framework is not only the initial carrier for keratinase but also the core for maintaining the three-dimensional spatial structure and catalytic activity of the enzyme molecule. To meet the specific physiological needs of pets and the preparation standards for high retention of keratinase activity, the selected main framework material must possess excellent low-temperature aqueous phase spreadability, enabling it to spontaneously form an encapsulating fluid under mild conditions. Secondly, it must also possess a cold cross-linking physical molding mechanism to solve problems such as enzyme molecule structure collapse and inactivation that are prone to occur in conventional microsphere frameworks.

[0037] Eight typical polymer materials in the current field of bio-embedding and formulation were selected as candidate materials. High-quality inner layer main framework materials were screened by detecting their low-temperature aqueous phase unfolding time, cold cross-linking curing time, three-dimensional geometric sphericity of microspheres, and spatial structure retention rate of keratinase.

[0038] Low-temperature aqueous phase expansion time assay: After stirring each candidate material powder in purified water at a temperature of 15 ℃ to 20 ℃, the time required for it to transform from a solid aggregate state to a homogeneous fluid state was recorded. This value characterizes the physical structure expansion efficiency of the polymer chain segments and is used to verify whether there is a risk of enzyme molecular structure collapse.

[0039] Cold crosslinking curing time test: Each material fluid was dropped into a crosslinking liquid at 4 ℃, and the time difference from the droplet contacting the low-temperature liquid surface to curing was recorded by high-frequency dynamic imaging. This value reflects the phase transition rate of the flexible long chain; the faster the rate, the stronger its ability to build a dense physical barrier.

[0040] 3D geometric sphericity testing of microspheres: The contour of the primary microsphere samples is scanned using a 3D morphology measuring instrument, and the ratio of the shortest diameter to the longest diameter of each microsphere boundary is calculated. This value characterizes the uniformity of the internal network stress and the density of the outer boundary during cross-linking molding. The closer the ratio is to 1, the more complete its physical framework and the absence of structural depressions.

[0041] Keratinase spatial structure retention rate detection: The solidified microspheres were disrupted to release the encapsulated enzyme molecules. The secondary and tertiary structure maps of the released enzyme were scanned using a circular dichroism spectroscopy (CD) instrument and overlaid onto the original enzyme powder map to calculate the percentage of spatial conformation retention. A higher retention rate indicates a more stable three-dimensional structure of the enzyme molecule.

[0042] The test results are as follows: Table 1

[0043] Among them, sodium carboxymethyl cellulose exhibited good low-temperature aqueous phase expansion time and enzyme spatial structure retention rate, but its cold cross-linking curing time was long and its roundness was low, which easily led to a large amount of free enzyme molecules being lost through penetration. Low-methoxyl pectin had good cold cross-linking curing ability, but its roundness was low and it was prone to structural depressions. Therefore, sodium alginate, which had better overall performance, was selected as the main framework material.

[0044] 1.2 Screening of dehydration proppant

[0045] After establishing sodium alginate as the inner framework, the low-temperature encapsulation of keratinase was initially achieved. However, the primary microspheres were filled with free water, which easily led to volume shrinkage and structural collapse after freeze-drying, resulting in failure of rapid disintegration and release. Therefore, a dehydration support agent was introduced to achieve efficient maintenance and anti-collapse reconstruction of the three-dimensional porous morphology of the microspheres without compromising the low-temperature encapsulation and high-activity locking of the main framework. This improved the deep dehydration processability of the targeted formulation and the final rapid disintegration performance in intestinal fluid.

[0046] By reviewing relevant literature, eight of the most typical and widely used freeze-drying excipients were selected for screening. The initial aqueous phase temperature of the system was standardized at 15–20 °C. After fixing the effective loading of keratinase and the nonionic surfactant, the selected dehydration support agents were compounded according to their optimal filling ratios: mannitol (12.50 wt%); maltodextrin (18.75 wt%); sucrose (15.20 wt%); lactose (16.45 wt%); dextran (8.60 wt%); glycine (10.35 wt%); polyethylene glycol 4000 (14.80 wt%); trehalose (15.50 wt%), with the remainder supplemented with sodium alginate. After solidifying and freeze-drying the above fluids, their dehydration anti-collapse index, target environment disintegration time, and enzyme spatial structure retention rate were measured to determine their microscopic dehydration support and structure maintenance effects.

[0047] Dehydration and Collapse Resistance Index Testing: After pre-freezing the solidified primary microspheres at -40 °C, they were sublimated and dehydrated in a vacuum at -10 °C. The three-dimensional geometric dimensions of the microspheres before and after water removal were scanned using industrial micro-CT scanning. The collapse resistance index was calculated as the percentage difference in volume shrinkage of the microspheres before and after dehydration. This value characterizes the spatial physical support rigidity provided by the support material to the sodium alginate cross-linked network, verifying whether the excipient can maintain the porous physical morphology inside the microspheres for a long time, preventing the pores from drying out and closing.

[0048] Targeted environmental disintegration time detection: Dehydrated and dried porous microspheres were immersed in a simulated pet intestinal test solution at 37°C, simulating intestinal peristalsis. A dynamic imaging recording system was used to continuously monitor the entire process of external liquid permeation towards the center. The time from microsphere contact with the liquid surface to the disintegration of its cross-linked network was recorded. This value can be used to verify whether the selected excipient can meet the response requirements for rapid release of the encapsulated material within the intestine.

[0049] The test results are as follows: Table 2

[0050] Mannitol exhibits strong anti-collapse ability, but its enzyme spatial structure retention rate is low, easily damaging the enzyme molecular structure and leading to its inactivation; dextran provides good protection for the enzyme molecular structure, but its disintegration time is long, which is not conducive to targeted and rapid release. Therefore, trehalose, which has a better overall effect in terms of anti-collapse, disintegration time, and structure retention rate, was selected as the dehydration support agent of this invention.

[0051] 1.3 Screening of Ionic Crosslinking Agents

[0052] While the composite system composed of sodium alginate and trehalose possesses good low-temperature cold stretching potential and anti-collapse properties during dehydration, the lack of three-dimensional physical constraints allows free enzyme molecules inside to easily diffuse outwards and escape. Therefore, by introducing an ionic crosslinking agent, the spatial charge properties of ions are used to guide the flexible polymer chains to fold, constructing a dense three-dimensional physical grid without disrupting the spatial conformation of the substrate, thus achieving the final structural shaping of the solid porous microspheres.

[0053] Six representative metal cations in the field of bio-embedding were selected for screening. The initial temperature of the composite liquid phase was uniformly set at 15–20 °C. The effective loading of keratinase, the amount of trehalose, and the amount of nonionic surfactant were fixed, with the remainder supplemented using sodium alginate. The above homogeneous composite fluid was then dropped into chloride aqueous solutions with the optimal molar concentration of the selected cations for cross-linking and curing. The cross-linking and curing effect of each metal cation was determined by measuring the cold cross-linking physical density of the primary microspheres, the effective shrinkage rate of the microporous network, and the enzyme spatial structure retention rate.

[0054] Cold crosslinking physical density test: A homogeneous composite fluid was uniformly dropped into a crosslinking solution at 4°C. After the droplet was completely submerged and underwent a short crosslinking process, a constant downward pressure deformation was applied to the surface of the primary microspheres using a microprobe, and the critical yield stress value at which micro-fracture occurred was recorded. This value characterizes the curing strength of the metal cation-driven long chains forming a three-dimensional physical network. The higher the critical yield stress, the stronger the densification ability of the crosslinking system.

[0055] Detection of effective shrinkage rate of microporous mesh: After rapid freezing and brittle fracture of primary microspheres using liquid nitrogen, the three-dimensional mesh morphology of their internal cross-section was observed using field emission scanning electron microscopy. The pore size was measured and the percentage of physical shrinkage was calculated. This value reflects the control of the coordination ability of specific metal cations on the spatial folding degree of polymer chain segments. It can verify whether the micropore size can embed and lock the trehalose support between physical nodes, thereby avoiding extrusion of excipients due to excessive shrinkage or loose structure due to insufficient shrinkage.

[0056] The test results are as follows: Table 3

[0057] As shown in the table, barium ions exhibit high cold crosslinking density, but their retention rate of enzyme spatial structure is low, easily leading to enzyme inactivation. Magnesium ions can achieve a high retention rate of enzyme spatial structure, but their low flexural stress prevents the long polymer chains from folding, resulting in a paste-like microsphere. Therefore, calcium ions, with better overall performance, were selected as the ionic crosslinking agent in this invention.

[0058] 1.4 Screening of the main material for the outer enteric coating

[0059] While the aforementioned preferred inner porous core possesses excellent dehydration resistance and rapid release potential, its microporous network makes it susceptible to gastric acid intrusion, thereby disrupting the spatial conformation of internal enzyme molecules. Therefore, an outer enteric coating is introduced, utilizing its conformational mutation effect to block gastric acid leakage pathways without damaging the inner porous framework, thus improving the gastric survival rate and intestinal targeted release performance of the porous targeted formulation.

[0060] Eight of the most representative conventional enteric coating materials in the fields of food and biodelivery were selected for screening. The aforementioned inner porous microspheres were placed in a micro fluidized bed coating device at a temperature ≤35 ℃, and the selected materials were uniformly sprayed and coated on the outer surface of the microspheres. The protective effect of each material was determined by measuring its swelling rate, the time for weak alkaline phase dissociation, and the retention rate of enzyme spatial structure.

[0061] Swelling rate determination: The coated composite microspheres were placed in simulated gastric fluid and shaken at low speed for 2 hours. The cross-section of the microspheres was observed using a laser confocal microscope, and the macroscopic swelling rate of the shell was read. The lower the swelling rate, the stronger its ability to resist physical penetration of acid.

[0062] Determination of disintegration time in weakly basic phase substances: Microspheres surviving in simulated gastric fluid were transferred to simulated intestinal fluid, and the morphological changes of the outer polymer membrane were continuously monitored using a high-speed dynamic imaging system. The time from contact with the weakly basic liquid surface to the rupture and peeling of the outer shell, exposing the porous channels of the inner layer, was recorded. The shorter the time, the faster the disintegration of the inner layer formulation is guaranteed.

[0063] The test results are as follows: Table 4

[0064] Among them, hydroxypropyl methylcellulose phthalate responds quickly to the dissociation of weakly basic substances, but has a high swelling ratio and a low spatial retention rate for enzymes, which easily leads to enzyme inactivation; refined shellac, although having a good swelling ratio, has a slow dissociation rate of weakly basic substances, which cannot meet the requirement of rapid disintegration. Therefore, corn gluten, which has a better overall effect in terms of swelling ratio, dissociation rate, and enzyme spatial retention rate, was selected as the main material for the outer enteric coating.

[0065] 1.5 Screening of Microscopic Flexible Sealing Agents

[0066] While the aforementioned enteric coating provides a core defense against acid-induced shrinkage and alkali-induced dissociation, the intense physical shrinkage of the long polymer chains inevitably induces micro-stress cracks on the outer shell surface. These micro-cracks become channels for acid leakage; furthermore, conventional small-molecule plasticizers are prone to structural dissolution in the liquid phase, leaving behind even more difficult-to-repair physical voids on the shell after detachment. Therefore, a specific micro-flexible sealing agent is introduced, utilizing its specific spatial volume and structural characteristics to prevent the formation of initial cracks while achieving non-detachment physical locking in a strong acid liquid phase.

[0067] Six microscopic flexible sealing agents with typical molecular volume and spatial segment conformation characteristics were selected for screening. Under uniform environmentally friendly solvent physical pre-dispersion and micro fluidized bed blending film formation conditions, the selected sealing agents were added to the film at their optimal filling ratios as follows: glycerol (3.15 wt%); polyethylene glycol (4.28 wt%); triethyl citrate (2.75 wt%); castor oil (1.82 wt%); chitosan (0.95 wt%); and fucoidan (2.15 wt%). The overall structural compatibility of each sealing agent was determined by measuring its anti-leakage rate, crack resistance strain, and pore dissolution rate.

[0068] Leakage prevention rate testing: The structure and cross-section of the acid-impregnated microspheres were dissected using a laser confocal microscope. The acid leakage prevention rate was calculated by reading the quenching area ratio of the pre-embedded fluorescent probes inside the microspheres. This value verifies whether the flexible sealing agent can eliminate the physical structural defects caused by microscopic physical voids in the outer shell, which lead to gastric acid intrusion and fatal damage to the internal enzyme spatial conformation.

[0069] Crack resistance strain rate test: The free blend coating film is subjected to uniaxial tensile sampling using a micro-property tester. The critical deformation displacement at the fracture extension is read and converted into crack resistance strain rate value to determine the micro-physical modification effect of the sealing agent molecules.

[0070] Pore ​​dissolution rate detection: The peripheral extreme acid test solution after soaking for 2 h was extracted by high performance liquid chromatography. The concentration of micro-sealing components free in the liquid phase was detected and the pore dissolution rate was calculated. This value can reflect whether each sealing agent can avoid structural displacement and escape in the micro gaps of the film layer.

[0071] The test results are as follows: Table 5

[0072] As shown in the table, polyethylene glycol exhibits strong resistance to cracking strain rate, but its high pore dissolution rate makes it ineffective in preventing gastric acid erosion. Triethyl citrate demonstrates strong static anti-permeation ability, enhancing the rigidity of the membrane layer, but resulting in poor resistance to cracking strain rate and susceptibility to physical breakage. Therefore, alginate oligosaccharides, with better overall performance, were selected as the micro-flexible sealing agent.

[0073] Example 2

[0074] Reference Figures 1 to 4 This is the second embodiment of the present invention. Having clarified the qualitative functions and microscopic spatial integration logic of the inner and outer double-layer core components, defining their quantitative proportions in the porous targeted delivery entity is the key to maximizing the mechanical support of the inner skeleton and balancing the spatial steric hindrance of the outer armor. Therefore, based on the baseline of the physical properties of each material determined by the aforementioned screening experiments, this embodiment further explores the optimal ratio of each component of the skeleton core and the outer barrier, aiming to obtain the optimal quantitative formulation that combines acid penetration defense with rapid disintegration by weak alkalis.

[0075] 2.1 Optimization of the ratio of trehalose to calcium ions

[0076] Having identified sodium alginate, trehalose, and calcium ions as the core components of the inner porous framework, the ratio of trehalose to calcium ions determines the initial framework rigidity and the integrity of the internal pore structure of the porous targeted formulation. If the proportion of calcium ions is too high, although it can significantly improve the density and shear stress resistance of the microstructure, it easily compresses and disrupts the three-dimensional conformation of the internal keratinase. If the proportion of trehalose is too high, although it can efficiently maintain the three-dimensional porous morphology of the microspheres and prevent collapse reconstruction, it easily dilutes the cross-linking points, leading to a loose and collapsed microsphere framework, which weakens its ability to resist subsequent processing shear forces. Therefore, it is necessary to find the optimal ratio of the two in terms of microscopic spatial physical integration.

[0077] After fixing the initial feed mass of standard keratinase stock solution and sodium alginate, the trehalose concentration was set from 1.0 to 5.0 wt% with a gradient step of 1.0 wt%; the calcium ion concentration was set from 0.5 to 2.0 wt% with a gradient step of 0.5 wt%. Experimental groups were set up by cross-variable setting, and the rigidity of the skeleton and the integrity of the internal pore structure of different ratios were evaluated by measuring the compressive yield strength, physical retention rate of three-dimensional micropores, and non-destructive loading rate of the initial conformation.

[0078] Compressive yield strength test: The microspheres are subjected to uniaxial compression sampling using an electronic universal physical property testing machine (texture analyzer). The maximum load-bearing peak value before physical brittle deformation is read and converted into compressive yield strength value. This determines the upper limit of rigid support provided by calcium ion coordination nodes at the macroscopic level, thereby avoiding the soft collapse defect of the microsphere skeleton.

[0079] Three-dimensional micropore physical retention rate detection: The microspheres were scanned by nitrogen adsorption-desorption using a fully automated specific surface area and porosity analyzer to calculate the three-dimensional micropore physical retention rate. This value characterizes the spatial occupancy feedback of the microchannels opened by trehalose molecules under vacuum sublimation phase transition stress in the porous framework system. The higher the retention rate, the more effectively the closure of the three-dimensional containment channels of the inner framework can be avoided.

[0080] Initial conformational non-destructive loading rate determination: Circular dichroism spectroscopy was used to continuously scan the characteristic polypeptide folding spectra of keratinase within the micropores. The conformational non-destructive loading rate, representing the deviation from the secondary physical structure, was extracted. This value characterizes the resistance to mechanical force feedback in the spatial folding state of the core enzyme molecule under the dual pressure of calcium ion cross-linking contraction and dehydration compression in the three-dimensional grid system. A higher non-destructive loading rate effectively avoids lethal conformational breakdown of the core active carrier before delivery caused by spatial coordination imbalance.

[0081] Test results are as follows Figure 1 , Figure 2 As shown, the compressive yield strength increases with increasing calcium ion concentration and decreasing trehalose concentration. Based on relevant data, the optimal compressive yield strength of the microsphere skeleton is found to be between 8 and 15 N. A bivariate nonlinear fitting was performed to obtain an optimal ratio range. Within this range, the extreme points of the physical retention rate of the three-dimensional micropores and the initial conformational undamaged loading rate were fitted, maximizing the extreme coordinates of the micropore retention rate (calcium ions 0.89 wt%, trehalose 3.32 wt%) and the extreme coordinates of the highest conformational undamaged loading rate (calcium ions 1.23 wt%, trehalose 2.56 wt%). To eliminate structural collapse or conformational strangulation defects caused by a single physical extreme value, the arithmetic mean of calcium ions 1.06 wt% and trehalose 2.94 wt% was taken as the theoretically optimal solution. Based on the weighing tolerance in industrial scale-up production, the optimal composite ratio of calcium ions 1.0 wt% and trehalose 3.0 wt% was selected.

[0082] 2.2 Optimization of the ratio of zeaxanthin to fucoidan

[0083] After establishing zein and fucoidan as the main material for the outer enteric coating and the micro-flexible sealing agent, respectively, their physical space ratio in the solid coating determines the density limit of the outer defense. If the proportion of zein is too high, although it can prolong the gastric acid penetration pathway, it will reduce the intestinal targeted disintegration rate; if the proportion of fucoidan is too high, although it can provide better micropore filling and stress relief effects, it may cause the outer shell to lose structural toughness and disintegrate. Therefore, it is necessary to explore the optimal balance point for the synergistic effect of the two.

[0084] The amount of zein added was set at 5.0–20.0 wt% of the total dry weight of the inner microspheres, with a gradient step of 5.0 wt%. The amount of fucoidan added was set at 5.0–25.0 wt% of the amount of zein added, with a gradient step of 5.0 wt%. Experimental groups were set up by cross-variables. The defensive effect of different coating ratios was evaluated by measuring the leakage prevention rate, the time for weakly basic phase dissociation, and the crack resistance strain rate of each group.

[0085] Test results as follows Figure 3 , Figure 4 As shown, with the increase of the outer baseline and the increase of the sealing agent proportion, the leakage prevention rate and crack resistance strain first rise and then fall, while the dissociation time continuously increases. To ensure that the microspheres have both the characteristics of resisting gastric acid erosion and rapid dissociation upon entering the intestine, the dissociation time of the weakly basic phase is generally within 15-30 min. Data fitting was performed to obtain an optimal ratio range. Within this range, the maximum gain of leakage prevention rate and crack resistance strain rate was optimized by differentiating and obtaining the following extreme points: leakage prevention rate (15.24 wt%, fucoidan 15.28 wt%) and crack resistance strain rate (14.82 wt%, fucoidan 16.42 wt%). To avoid defects such as barrier thinning or internal stress cracking caused by unidirectional imbalance, the arithmetic average of 15.03 wt% corn gluten and 15.84 wt% fucoidan was taken as the optimal ratio. Based on the precision tolerance of industrial mass production, the optimal ratio was finally selected as 15.0 wt% corn gluten added to the inner microspheres and 15.0 wt% fucoidan added to the corn gluten.

[0086] Example 3

[0087] Reference Figures 5 to 10 This is the third embodiment of the present invention. This embodiment aims to optimize the process flow and correct the parameters of the preferred formulation determined in the laboratory. Although the aforementioned experiments have locked in the optimal ratio of the inner and outer core components, the process of scaling up from laboratory-scale trials to large-scale industrial production is often accompanied by severe phase separation and uneven heat and mass transfer. In particular, the mechanically and thermally sensitive steps involved in this formulation, such as the freeze-drying of the inner porous framework and the low-temperature atomization spraying of the outer layer, can easily lead to the amplification of microstructural defects due to changes in the physical field, thereby affecting the final activity and stability of the core enzyme preparation. Therefore, it is necessary to optimize the core processing parameters in the large-scale production stage to ensure that ton-scale production can be achieved.

[0088] 3.1 Processing optimization of stirring speed and time

[0089] First, sodium alginate and 3.0 wt% trehalose are sequentially pumped into a stirred tank for dissolution. Based on engineering experience and process consensus in protein-based active formulations, to ensure the lossless transfer of core enzyme molecules during ton-scale scaling and to avoid thermal collapse catastrophe, the material temperature throughout the solid-liquid dispersion stage is generally maintained at 15–20 °C. After determining the reaction temperature, the energy input matrix formed by the stirring rate and time is a key control point affecting the performance of the final product.

[0090] Therefore, the system temperature was controlled at 15~20 ℃, and 15.0 wt% of the total dry weight of keratinase powder in the inner layer was slowly added to the completely dissolved high-viscosity colloid. The stirring speed was controlled from 100~500 rpm with a gradient step of 100 rpm; the stirring time was controlled from 10~60 min with a gradient step of 10 min. Experimental groups were set up by cross-variable, and the processing effect of different stirring speeds and times was evaluated by using viscosity retention rate, enzyme spatial structure retention rate, and homogenization disintegration rate.

[0091] Viscosity retention rate determination: Under standard operating conditions, the apparent dynamic viscosity of the fluid was measured using a rotational rheometer. The viscosity retention rate of the fluid relative to the initial colloidal matrix was extracted and output. This value characterizes the tear resistance and physical integrity feedback of sodium alginate in a composite mechanical stress field. A higher retention rate indicates a more sufficient shear response of the polymer entanglement network, and a more effective prevention of the collapse of the inner porous framework caused by hydrodynamic mechanical degradation.

[0092] Homogeneous Disintegration Rate Determination: Under standard pressure filtration conditions, an industrial sieve is used to physically retain and weigh equal volumes of dispersed fluid. The homogeneous disintegration rate, representing the percentage of fully hydrated and digested powder in the total fed mass, is extracted and output. This value characterizes the solid-liquid interface hydration response where mechanical shear energy overcomes colloidal viscous resistance and breaks the surface tension of the dry powder. A higher disintegration rate indicates more thorough spatial stripping and free penetration of the powder in the liquid phase, effectively preventing voids in the inner film structure.

[0093] Test results are as follows Figure 5 , Figure 6As shown, with the increase of stirring speed and time, the homogenization disintegration rate continuously increases, and the dry powder interface is rapidly torn and hydrated; however, due to the physical strangulation caused by mechanical stress, both viscosity retention and enzyme spatial conformation retention rate show a decreasing trend. To achieve a balance between macroscopic powder homogeneous embedding and microscopic polymer / protein structure preservation, three-dimensional surface cross-fitting was performed on the response data of these three core structures. After stripping away the low-frequency insoluble region and the high-frequency catastrophe region, the theoretical optimal intersection coordinate point that can simultaneously satisfy extreme interface hydration and lossless structural transfer was calculated: stirring speed 298.46 rpm, time 39.61 min. Considering the parameter setting of large-scale mixers in industrial mass production and the convenience of engineering calibration for batch operations, the theoretical extreme value was rigorously rounded down by engineering, and the optimal processing parameters for inner layer solid dispersion were finally locked as: stirring speed 300 rpm and time 40 min as the optimal dispersion processing parameters.

[0094] 3.2 Curing Time Optimization

[0095] After complete dispersion, the homogeneous fluid is slowly dripped into an aqueous solution of calcium chloride containing 1.0 wt% calcium ions, which has been pre-cooled to 4 °C, and allowed to stand and solidify continuously.

[0096] Curing time is a key kinetic variable determining the physical cross-linking and porous framework formation of sodium alginate from the liquid phase to the solid phase. If the curing time is too short, calcium ions cannot fully penetrate the droplets, leading to spatial collapse and cracking during subsequent cold drying and dehydration. If the curing time is too long, it will cause strong internal shrinkage of the microspheres, resulting in a loss of swelling responsiveness. Therefore, it is essential to find an optimal curing time that provides strong compressive support without causing excessive structural shrinkage.

[0097] The system temperature was controlled at 4 ℃, and the curing time ranged from 10 to 60 min. Six experimental groups were set up with a gradient step of 10 min. The cold-drying collapse rate of the microporous skeleton, the intestinal fluid targeted swelling response rate, and the enzyme activity retention rate of different groups were detected to evaluate the process effect of different curing times.

[0098] Determination of the cold-drying collapse rate of the microporous framework: The cured primary microspheres were freeze-dried, and the microspheres before and after dehydration were scanned in situ using a three-dimensional morphology analyzer. The volume shrinkage ratio and surface deformation extreme values ​​were extracted and output. This collapse rate characterizes the physical depth of calcium ion penetration into the polymer droplet and the three-dimensional mechanical support effectiveness of the sodium alginate cross-linked network. The lower the collapse rate, the better the penetration of the cross-linked network, and the more effectively it can prevent catastrophic structural collapse.

[0099] Intestinal fluid targeted swelling response rate determination: The cold-dried finished microspheres were immersed in simulated pet intestinal fluid. An optical swelling meter was used to track and record the volume expansion factor and phase transition trajectory of the microspheres after water absorption. This swelling rate reflects the spatial network expansion ability and physical pore retention state of the porous framework inside the microspheres. A higher swelling rate ensures better release of the core macromolecular enzyme.

[0100] Enzyme activity retention assay: The keratinase retention activity of the finished microspheres was measured using a biochemical analyzer under a specific substrate colorimetric system. This value reflects the micromechanical survival state of the core protein's secondary fold conformation during intense dehydration and shrinkage. A higher retention rate indicates less disruption to protein hydrogen bonds, thus better preserving enzyme activity.

[0101] Test results as follows Figure 7 As shown, with the increase of curing time, both the swelling response rate and enzyme activity retention rate show a trend of first increasing and then decreasing, while the collapse rate shows an L-shaped decline. Data fitting was performed on the maximum gain effect of swelling rate and enzyme activity retention rate to obtain an optimal molding survival range. Within this range, the critical extreme point of collapse rate was fitted, and its extreme point was found to be at 31.03 min. Based on the convenience of workshop calibration and flow control in industrial-scale production, 30 min was finally selected as the optimal curing time.

[0102] 3.3 Processing optimization of pre-freezing and drying temperatures

[0103] First, the washed primary microspheres are spread evenly in a freeze dryer for dehydration and solidification. Since this stage does not involve secondary chemical cross-linking of the polymer backbone, it is only necessary to sublimate and remove the free water in the system under vacuum. After establishing this physical structural defense, the thermodynamic composite phase transition matrix formed by the pre-freezing endpoint temperature and the primary drying partition temperature is the key node determining the performance of the finished product.

[0104] Therefore, the pre-freezing temperature was controlled at -50 to -20 ℃ with a gradient step of 5 ℃; the drying temperature was controlled at -30 to 0 ℃ with a gradient step of 5 ℃. Experimental groups were set up by cross-variables, and the process effect of each group was evaluated by using the microstructure space collapse rate, wear resistance pulverization rate and single batch sublimation drying time.

[0105] Microstructure spatial collapse rate determination: In-situ scanning of the molded microspheres was performed using a three-dimensional morphology microscope to determine the volume collapse ratio and surface deformation of the microspheres before and after sublimation. This value reflects the three-dimensional mechanical solidification effectiveness of the polymer support framework inside the microspheres during the pre-freezing and drying stages. The smaller the value, the more effectively internal pore closure and spatial structure collapse can be avoided.

[0106] Wear-resistant fragmentation rate determination: Microspheres are placed in a fluidized bed for mechanical impact, then sieved and the mass percentage of detached and broken powder is measured. This value reflects the mechanical resistance of the microsphere shell to physical shearing and hard impact from airflow. The smaller the value, the more effectively the risk of brittle fragmentation and core load leakage can be avoided in the subsequent enteric coating stage.

[0107] Single-batch sublimation drying time measurement: During the freeze-drying dehydration process under vacuum, the time required from the start of the drying temperature rise to the chamber pressure reaching the complete dehydration equilibrium baseline is measured by comparing the pressure difference in real time using a Pirani vacuum gauge and a capacitance diaphragm gauge. The shorter the time, the more effectively equipment stagnation and long-cycle energy overload can be avoided in industrial-scale mass production.

[0108] Test results as follows Figure 8 , Figure 9 As shown, with increasing temperature, the microscopic spatial collapse rate continuously increases after exceeding the thermodynamic critical point, while the drying time continuously decreases, and the wear-resistant pulverization rate shows a trend of first decreasing and then increasing. A continuous nonlinear spatial surface fitting was performed on the minimum safe regions of the collapse rate and wear-resistant pulverization rate, yielding a safe interval with both low collapse rate and pulverization risk. Within this interval, the extreme point of drying time was fitted, revealing that the extreme point is located at a pre-freezing temperature of -39.67℃ and a drying temperature of -11.41℃. Based on the standard refrigeration energy efficiency node of industrial large-scale freeze dryers, the optimal reaction temperature was finally selected as a pre-freezing temperature of -40℃ and a drying temperature of -10℃.

[0109] 3.5 Optimization of outer coating weight gain rate

[0110] 15.0 wt% of zein and 15.0 wt% of fucoidan were dissolved in 70% ethanol aqueous solution to prepare a coating fluid, which was then used to bottom-coat the freeze-dried primary microspheres. The surface temperature of the material was controlled at 15~18℃, and the hydrophobic protein was interwoven and formed on the outside of the porous framework of the microspheres by atomization spraying, finally producing finished bilayer microspheres with different spatial defense depths.

[0111] The coating gain rate is a core physical variable that determines the density of the outer armor and the depth of space defense. If the gain rate is too low, it is easily penetrated by gastric acid and killed by core enzymes; if the gain rate is too high, it may cause the microspheres to disintegrate slowly in the intestine and lose their targeted release properties. Therefore, it is necessary to find an optimal coating gain rate that can provide acid-resistant physical isolation without causing spatial lock-in in the intestine.

[0112] The coating weight gain rate was set at 5-30 wt%, with a gradient step of 5 wt%, and 6 experimental groups were set up. The enzyme spatial conformation retention rate, intestinal fluid targeted swelling response rate and micro-armor surface porosity defect rate of different groups were detected to evaluate the process effect of different coating weights.

[0113] Determination of porosity defect rate on micro-armor surface: In-situ magnified scanning of microsphere samples before and after fluidized bed coating was performed using a high-resolution scanning electron microscope. Image topology analysis software was used to extract and calculate the proportion of the projected area of ​​residual microcracks, unclosed pinholes, and phase interfaces on the outer shell surface to the total surface area of ​​the microspheres. The smaller the proportion, the stronger the macroscopic acid resistance.

[0114] Test results are as follows Figure 10 As shown, with the increase of coating weight gain rate, the enzyme spatial conformation retention rate increases, while the intestinal fluid-targeted swelling response rate and the micro-armor surface porosity defect rate decrease. To achieve a physical-mechanical balance between strong acid physical defense and rapid intestinal disintegration, a nonlinear dual-objective overlapping region fitting was performed on the enzyme spatial conformation retention rate and the intestinal fluid-targeted swelling response rate to obtain an optimal weight gain range. Within this range, the minimum value of the micro-armor surface porosity defect rate was fitted and optimized, and its minimum value was found to be at 20.34 wt%. Finally, based on the peristaltic pumping tolerance and temperature control calibration of industrial-scale fluidized bed equipment, 20 wt% was ultimately selected as the optimal coating weight gain rate.

[0115] Example 4

[0116] Reference Figure 11 This is the fourth embodiment of the present invention. This embodiment provides a method for preparing a microsphere-coated keratinase-targeted delivery formulation that responds to the intestinal environment, specifically including the following steps: S1. Homogeneous dispersion in liquid phase

[0117] By weight, 81 parts sodium alginate, 3 parts trehalose, and 15 parts keratinase were added to an appropriate amount of liquid medium. The homogenizing and stirring equipment was started, the speed was set to 300 rpm, and the homogenizing and stirring were continued for 40 min to promote the complete deentanglement of macromolecular chain segments in space, so as to obtain a highly uniform liquid-phase enzyme dispersion. S2. Low-temperature physical curing and free ion stripping

[0118] Lower the system temperature to 0-4 °C, and uniformly drop the liquid enzyme dispersion into 1 part of calcium ion aqueous solution, allowing it to stand and solidify for 30 min. After solidification, filter out the initially formed microspheres and rinse them three times with cold purified water at 4 °C to completely remove the free calcium ions attached to the surface of the framework, obtaining washed microspheres; S3. Microscopic spatial freeze-drying pore structure

[0119] The washed microspheres were spread out and fed into a freeze dryer for dehydration and pore formation. In the first stage, in-situ pre-freezing was performed at a constant cooling rate of 1.0–2.0 °C / min, cooling the material to -40 °C and maintaining this temperature for 2–4 h, allowing internal moisture to crystallize into a template. In the second stage, a vacuum pump was activated, reducing the system vacuum to 10–20 Pa while simultaneously raising the partition temperature to -10 °C, for a first sublimation drying process of 12–24 h. Finally, the system vacuum was reduced to 1–5 Pa for a second desorption drying process of 4–8 h. Through the sublimation of ice crystals, porous framework microspheres with intact porous support channels were obtained. S4. Preparation of physically coated fluids

[0120] Add 15 parts of corn gluten and 2.5 parts of fucoidan oligosaccharide to a 70% ethanol aqueous solution and stir at room temperature until the long polymer chains are completely physically extended and dissolved to obtain a uniform coated fluid. S5. Dense outer armor coating

[0121] The porous framework microspheres were fed into a bottom-spray fluidized bed coating machine, and coating fluid was sprayed at 15-18 °C, with the final coating amount of the outer layer controlled to be 20 parts. After spraying, the liquid path was cut off, and in-situ cold air was continuously used for fluidized drying for 15 min to remove the solvent and solidify the spatial network of the outer shell formed by corn gluten and fucoidan, finally obtaining the finished bilayer microspheres.

[0122] The prepared targeted delivery formulation has the following characteristics: pore defect rate 2.8%, enzyme spatial conformation retention rate 92.3%, targeted swelling response rate 89.6%, core enzyme activity leakage rate 3.8%, final cumulative release rate 98.2%, relative enzyme activity retention rate 95.32%, and mechanical compressive strength 2.15 MPa.

[0123] In summary, by constructing an inner porous framework and a natural protein outer layer, we can improve the problem of keratinase being easily deactivated due to spatial structural collapse during processing, as well as the physical structure control problem of microspheres being unable to simultaneously achieve strong anti-acidity in the stomach and rapid disintegration in the intestine.

[0124] Specifically, this process uses a sodium alginate system as the inner framework, utilizing trehalose to provide in-situ support for the interconnecting channels. Keratinase is dispersed at 15–20 °C, and then solidified by being dropped into a 4 °C environment. This avoids damage to the three-dimensional structure of the enzyme molecules caused by high temperatures, and the initial activity of the enzyme is locked and preserved through a three-dimensional network structure. Based on this, freeze-drying dehydration creates a highly porous physical morphology for the inner microspheres, ensuring rapid disintegration of the microspheres in the intestine. Finally, zein is densely encapsulated on the outside of the microspheres at 15–18 °C. The use of fucoidan intercalation and sealing of microscopic topological defects during the zein film formation process prevents secondary inactivation caused by high-temperature film formation. This outer shell effectively blocks gastric acid and rapidly disintegrates upon entering the intestine. The synergistic effect of the inner and outer double-layer physical structures achieves targeted intestinal delivery of keratinase.

[0125] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit it. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the spirit and scope of the technical solutions of the present invention, and all such modifications or substitutions should be covered within the scope of the claims of the present invention.

Claims

1. A preparation process for a microsphere-coated keratinase-targeted delivery formulation that responds to the intestinal environment, characterized in that, Includes the following steps: S1. By weight, add 75-85 parts sodium alginate, 2-5 parts trehalose and 10-20 parts keratinase to the liquid medium and homogenize and stir at 100-500 rpm for 30-50 min to obtain the liquid enzyme dispersion. S2. Lower the system temperature, drop the liquid-phase enzyme dispersion into 0.5-2 parts of calcium ion aqueous solution and solidify for 20-40 min. Wash the solidified microspheres to obtain washed microspheres. S3. The washing microspheres are spread out and fed into a freeze dryer for freeze drying. They are pre-frozen in situ at -50~-30 ℃, and then the temperature of the partition is raised to -20~0 ℃ under vacuum for dehydration and drying to obtain porous framework microspheres. S4. Dissolve and homogenize 10-20 parts of corn gluten and 1-5 parts of fucoidan in a 70% ethanol aqueous solution to obtain a coated fluid; S5. Control the surface temperature of the material, spray the coating fluid onto the porous skeleton microspheres, and control the outer coating to be 15-25 parts. After in-situ cold air continuous fluidization drying, the finished double-layer microspheres are obtained.

2. The method for preparing a microsphere-coated keratinase-targeted delivery formulation that responds to the intestinal environment according to claim 1, characterized in that, In step S1, the sodium alginate is 81 parts by weight, the trehalose is 3 parts by weight, and the keratinase is 15 parts by weight; the homogenization stirring parameters are 300 rpm for 40 min.

3. The method for preparing a microsphere-coated keratinase-targeted delivery formulation that responds to the intestinal environment according to claim 1, characterized in that, In step S2, the calcium ion aqueous solution is 1 part by weight; the curing time is 30 min.

4. The method for preparing a microsphere-coated keratinase-targeted delivery formulation that responds to the intestinal environment according to claim 1, characterized in that, In step S3, the in-situ pre-freezing temperature is -40 ℃, and the dehydration and drying temperature is -10 ℃.

5. The method for preparing a microsphere-coated keratinase-targeted delivery formulation that responds to the intestinal environment according to claim 1, characterized in that, In step S4, the weight parts of the corn gluten are 15 parts, and the weight parts of the fucoidan oligosaccharide are 2.5 parts.

6. The method for preparing a microsphere-coated keratinase-targeted delivery formulation that responds to the intestinal environment according to claim 1, characterized in that, In step S2, the system temperature needs to be reduced to 0~4℃.

7. The method for preparing a microsphere-coated keratinase-targeted delivery formulation that responds to the intestinal environment according to claim 1, characterized in that, In step S2, the washing process is as follows: the microspheres are filtered out and rinsed three times continuously with cold purified water at 4 °C.

8. The method for preparing a microsphere-coated keratinase-targeted delivery formulation that responds to the intestinal environment according to claim 1, characterized in that, In step S3, the parameters for freeze-drying are: The first stage involves in-situ pre-freezing at a cooling rate of 1.0~2.0 ℃ / min for 2~4 h; the second stage involves starting the vacuum pump to reduce the system vacuum to 10~20 Pa and performing sublimation drying for 12~24 h; finally, the system vacuum is reduced to 1~5 Pa and a second drying is performed for 4~8 h.

9. The method for preparing a microsphere-coated keratinase-targeted delivery formulation that responds to the intestinal environment according to claim 1, characterized in that, In step S5, the surface temperature of the controlled material needs to be controlled at 15~18 ℃, and the in-situ cold air continuous fluidization drying time is 15 min.

10. A microsphere-coated keratinase-targeting delivery formulation that responds to the intestinal environment, prepared by any one of claims 1 to 9, characterized in that, The keratinase-containing bilayer microspheres have a core-shell nested three-dimensional structure, with a porous network formed by the physical coordination of sodium alginate and calcium ions and the interpenetration of trehalose molecules as the inner matrix framework; the keratinase entities are uniformly distributed in the spatial channels of the porous network in a free state. Hydrophobic zein macromolecular segments are physically interwoven and wrapped around the inner matrix backbone to form a dense outer enteric coating, and fucoidan oligosaccharides are embedded and sealed within the microscopic topological defects of the dense outer coating.